Sustainable Da'wah through Social Entrepreneurship: Transforming Islamic Philanthropy from Charity to Empowerment - Muhammad Ridlo Zarkasyi; Meitria Cahyani; Yulizar Djamaluddin Sanrego (Institut Agama Islam Negeri Ponorogo, 2026)
This study examines how social entrepreneurship can be conceptualized as an evolutionary model of sustainable da'wah by transforming Islamic philanthropy from charity-based assistance into empowerment-oriented development. Employing a normative-conceptual research design, the study uses a systematic literature review of scholarly works on da'wah bil-ḥāl, Islamic philanthropy, and social entrepreneurship published between 2000 and 2026. Data were analyzed using qualitative content analysis and descriptive-critical analysis to synthesize the conceptual relationships among the three domains. The findings reveal that da'wah bil-ḥāl, Islamic philanthropy, and social entrepreneurship share a common orientation toward community empowerment while performing complementary functions: da'wah bil-ḥāl provides the normative foundation, Islamic philanthropy mobilizes social resources, and social entrepreneurship operationalizes sustainable value creation. Based on this synthesis, the study proposes a Sustainable Da'wah through Social Entrepreneurship framework linking Islamic values, philanthropic capital, entrepreneurial innovation, community empowerment, self-reliance, collective well-being, and falāḥ. The framework contributes to contemporary Islamic economics and Islamic social finance by offering a novel theoretical model that repositions Islamic philanthropy as a sustainable mechanism for long-term socio-economic transformation.